The Analgesic Effect of Pineapple Fruit Juice on Mice - Ainul Atiqah binti Hilmi; Vycke Yunivita KD; Henny Anggraini Sadeli (Faculty of Medicine Universitas Padjadjaran, 2014)
Background: Pain is a feeling stimulated by the nervous system which can be suppressed by giving an analgesic agent. Some studies revealed that pineapples have an analgesic effect. This study aim was to determine analgesic effect of pineapple on mice.Methods: In this experimental study, the effect was examined by using a writhing method on the 28 male mice. Subjects were divided into 4 groups with 7 mice each. The control group received aquades and other groups received pineapple fruit juice with 20%, 40% and 80% concentration with the dosage of 10 mL/kg/body weight. After 30 minutes, 3% acetic acid was injected intraperitoneally to induce pain. Writhing responseswere observed every 5 minutes for 30 minutes.Results: The result for mean of total writhing reaction was 2.39±0.40, 1.92±0.40, 1.50±2.13, 1.66±0.11 respectively for group 1 to 4. These data indicated a significant decrease of total writhing response in mice with 20%, 40% and 80% concentration compared to control group (p=0.023;p=0.000 and p=0.000 respectively). Most optimal concentration was40% with the protective percentage equal to 71.8%.Conclusion: Pineapple fruit juice concentrations (20%, 40%, and 80%has an analgesic effect with the most optimal concentration of 40%.Keywords: analgesic, pain, pineapple fruit, writhing method Efek Analgesik Jus Buah Nanas Pada Mencit Latar Belakang: Nyeri adalah sensasi perangsangan sistem saraf yang dapat ditekan dengan pemberian zat analgetik. Penelitian sebelumnya menemukan bahwa nanas memiliki efek analgesik. Tujuan penelitian ini adalah untuk mengetahui efek analgesik nanas pada mencit.Metode: Efek analgesik diperiksa dengan menggunakan metode “writhing“ pada 28 mencit jantan. Subyek penelitian dibagi menjadi 4 kelompok masing-masing 7 ekor. Kelompok kontrol menerima aquades dan kelompok lainnya menerima jus buah nanas secara oral dengan konsentrasi 20%, 40% dan 80% dengan dosis 10 mL/kg/berat badan. Setelah 30 menit, asam asetat 3% disuntikkan intra peritoneal untuk menginduksi nyeri. Respons “writhing” diamati setiap 5 menit selama 30 menit.Hasil: Hasil rata-rata reaksi total ”writhing”adalah 2.39 ± 0.40, 1.92 ± 0.40, 1.50 ± 2.13, 1.66 ± 0.11 masing-masing untuk kelompok 1 sampai 4. Data ini menunjukkan penurunan yang signifikan dari jumlah respon ”writhing” pada tikus dengan 20%, 40 % dan konsentrasi 80% dibandingkan dengan kelompok kontrol (p=0,023; p=0,000; dan p=0,000masing-masing). Konsentrasi optimal adalah 40% dengan persentase pelindung sebesar 71,8%.Simpulan: Konsentrasi jus buah nanas (20%, 40% dan 80%) memiliki efek analgesik dengan konsentrasi paling optimal pada 40%.Kata Kunci: analgesik, nyeri, nanas, writhingDOI: 10.15850/amj.v1n2.356